Visualizing Acoustic Space - Ouzounian, Gascia (Circuit)

(untitled) (Les Presses de l'Université de Montréal, 2007)
AbstractThis article explores concepts of acoustic space in postwar media studies, architecture, and spatial music composition. A common link between these areas was the characterization of acoustic space as indeterminate, chaotic, and sensual, a category defined in opposition to a definite, ordered, and rationalized visual space. These conceptual polarities were vividly evoked in an iconic sound-and-light installation, the Philips Pavilion at the 1958 Brussels World Fair. Designed by Le Corbusier, the Philips Pavilion also featured a black-and-white film, color projections, hanging sculptures, and Edgard Varèse’s Poème électronique, a spatial composition distributed over hundreds of loudspeakers and multiple sound routes. Typically remembered as a sequence of abstract sound geometries, the author argues that Poème électronique was instead an allegorical work that told a “story of all humankind.” This narrative was expressed through a series of conceptual binaries that juxtaposed such categories as primitive/enlightened, female/male, racialized/white, and sensual/ rational– contrasts that were framed within the larger dialectic between acoustic and visual space.